Clustering in the stellar abundance space. Issue 3 (24th October 2017) - Boesso, R; Rocha-Pinto, H J
Abstract: We have studied the chemical enrichment history of the interstellar medium through an analysis of the n -dimensional stellar abundance space. This work is a non-parametric analysis of the stellar chemical abundance space. The main goal is to study the stars from their organization within this abundance space. Within this space, we seek to find clusters (in a statistical sense), that is, stars likely to share similar chemo-evolutionary history, using two methods: the hierarchical clustering and the principal component analysis. We analysed some selected abundance surveys available in the literature. For each sample, we labelled the group of stars according to its average abundance curve. In all samples, we identify the existence of a main enrichment pattern of the stars, which we call chemical enrichment flow . This flow is set by the structured and well-defined mean rate at which the abundances of the interstellar medium increase, resulting from the mixture of the material ejected from the stars and stellar mass-loss and interstellar medium gas. One of the main results of our analysis is the identification of subgroups of stars with peculiar chemistry. These stars are situated in regions outside of the enrichment flow in the abundance space. These peculiar stars show a mismatch in the enrichment rate of a few elements, such as Mg, Si, Sc and V, when compared to the mean enrichment rate of the other elements of the same stars. We believe that the existence of these groups of stars with peculiar chemistry may be related to the accretion of planetary material on to stellar surfaces or may be due to production of the same chemical element by different nucleosynthetic sites.